Feasibility of Patient-Reported Outcomes Measurement Information System (PROMIS®) computerized adaptive tests in systemic lupus erythematosus outpatients. (September 2018) - Kasturi, S; Burket, J C; Berman, J R; Kirou, K A; Levine, A B; Sammaritano, L R; Mandl, L A
Objective: The aims of this study were to assess the feasibility of administering Patient-Reported Outcomes Measurement Information System (PROMIS®) computerized adaptive tests (CATs) to outpatients with systemic lupus erythematosus (SLE). Methods: Adults with SLE were recruited during routine outpatient visits at an SLE Center of Excellence. Participants completed 14 PROMIS CATs and provided feedback on their experience. Differences in socio-demographic and clinical characteristics between participants and non-participants were evaluated. Results: A total of 204 (86%) of 238 socioeconomically and racially diverse SLE patients completed PROMIS CATs. There were no significant differences between participants and non-participants. Time constraints were cited most frequently as reasons for non-participation. More than 75% of individuals submitted positive comments, including approval of the content and format of questions, and the survey's promotion of self-reflection. A minority of participants cited challenges, most often related to question phrasing (8%) and technical difficulties (6%). Conclusions: The administration of PROMIS CATs was feasible and positively received in a diverse cohort of SLE outpatients. Neither socio-demographic nor disease characteristics were significant barriers to successful completion of PROMIS CATs. PROMIS CATs have great potential for efficiently measuring important patient-centered outcomes in routine clinical care of a wide range of SLE patients.